Impact of different pre-treatment strategies on the quality of fatty acid composition, tocols content & metabolic syndrome related activities of Perilla frutescens seed oil - Sasithorn Sirilun, Bhagavathi Sundaram Sivamaruthi, Noppawat Pengkumsri, Manee Saelee, Khontaros Chaiyasut, Nucharee Tuntisuwanno, Maitree Suttajit, Sartjin Peerajan, Chaiyavat Chaiyasut (Journal of Applied Pharmaceutical Science, 2016)
Perilla frutescens (Nga-Mon) is an annual herbaceous plant, reported for its antioxidant, anti-allergic, anti-inflammatory and neuroprotective properties. The current study was conducted to compare the different pre-treatment techniques followed by hexane extraction for perilla seed oil and its pharmaceutical values. There are no significant differences in the yield of seed oil after pre-treatments except sonication. All the pre-treatments diminish the endogenous lipase activity, peroxidation and degradation of the oil. Fatty acid content analysis revealed that the nutrient quality, with respect to fatty acid content, of perilla seed was not compromised with any of the pre-treatments of current study. The results of α- amylase, α- glucosidase and protein glycation inhibition assays suggested that tested perilla seed oils are pharmaceutical candidate for the treatment of carbohydrate related diseases, especially for diabetes. Selection of appropriate pre-treatment strategies will helps to extract the perilla seed oil without any compromise in its quality. The current study suggested that moist heat with pressure can be an appropriate pre-treatment method for perilla seed oil extraction.
Keywords: Perilla frutescens,Pre-treatment,lipase,Tocols,Metabolic syndrome.